Applications of Circulating Tumor DNA in Immune Checkpoint Inhibition: Emerging Roles and Future Perspectives - Lu, Chang; Zhang, Yi-Chen; Chen, Zhi-Hong; Zhou, Qing; Wu, Yi-Long (Frontiers in Oncology, 2022)
Immune checkpoint inhibitors (ICIs), especially anti-PD-1/PD-L1 antibodies, have made dramatic progress in treatment of lung cancer, especially for non-oncogene driven patients. However, responses are limited to a subset of patients, and which subset of patients will beneﬁt from ICI remains unknown. With the advantage of minimally invasive, dynamic monitoring, non-invasive biomarkers appear as promising candidates to predicting response, monitoring resistance and tracking evolution of lung cancer during ICIs treatment. In the present review, we summarize predictive non-invasive biomarkers. We examine the potential of pre- and on-treatment features, alongside multiparameter models integrating non-invasive biomarkers of ICIs. We further discuss roles of liquid biopsies in monitoring treatment resistance, as well as challenges in clinical translation.